Strain Hardening Behavior of Engineered Geopolymer Composites: Effects of the Activator Combination - Nematollahi, B.; Sanjayan, J.; Shaikh, Faiz (Australian Ceramic Society, 2015)
Fly ash-based engineered geopolymer composites (EGCs) exhibiting strain hardening behavior under uni-axial tension were developed employing two different sodium-based (Na-based) and potassium-based (K-based) activator combinations. The relatively brittle low calcium (Class F) fly ash-based geopolymer matrix was reinforced with randomly oriented short poly vinyl alcohol (PVA) fibers (2% v/v). Na-based activator combination was composed of 8.0 M NaOH solution (28.6% w/w) and Na2SiO3 solution (71.4% w/w) with a SiO2/Na2O ratio of 2.0; whereas, Kbased activator combination was composed of 8.0 M KOH solution (28.6% w/w) and K2SiO3 solution (71.4% w/w) with a SiO2/K2O ratio of 2.23. The matrix and composite properties of the developed fly ash-based EGCs including workability of the fresh matrix, density, compressive strength and uni-axial tensile behavior were evaluated. The experimental results revealed that the sodium-based EGC (EGC-Na) exhibited superior tensile strain capacity, compressive and uni-axial tensile strengths with significantly enhanced ductility.